Perancangan dan Konstruksi Mesin Sortasi dan Pemutuan Buah Jeruk dengan Sensor Kamera CCD - Usman Ahmad; Rudy Tjahjohutomo; Mardison S. (PERTETA, 2008)
Citrus is one of important fruits in Indonesia and its production increases every year. However, postharvest equipment for citrus is very limited, leading to low postharvest technology utilization. The objective of this research was to develop a real-time quality evaluation system using a color CCO camera, to be used as an image sensor and processing unit for quality evaluation of the citrus from acquired image. The system consists of a color CGO camera, a computer with an image frame grabber, an image acquisition chamber, a logic control panel, and a software to run all the installed hardware Some important parameters of visual quality of citrus were studied. Five groups of different quality of citrus, obtained from a big trader in Pasar Induk Kramatjati, were used for samples. The images were captured and then analyzed with image processing program using area projectio and RGB and HSI color model algorithms, for the fruit size and color respectively. The results were analyzed to determine whether there were parameters that correlates with weight, sweetness and firmness, to be used for quality evaluation. Visual parameters that figures the real quality of citrus best were then selected to be used for quality parameters to develop a real-time quality evaluation system for citrus in the next step.Keywords: image processing, sortasi, pemutuan, otomatis Diterima: 15 Oktober 2007; Disetujui: 18 Pebruari 2008